Nonlinear dynamics of exchange rate returns: A multi-country experience - Wali, Muammer; Chan, Felix; Manzur, Meher (School of Economics and Finance, Curtin Business School, Curtin University, 2011)
This paper examines the presence of nonlinear behavior in exchange rates of 31 countries, majority of which are less liquid in the foreign exchange market and maintain a floating exchange rate system. The results, based on formal test procedures, provide evidence of nonlinear behavior in the residuals from both structural and time series models of exchange rates. The results also indicate that standard serial correlation test alone may not be useful to validate correct model specification as it has low power against nonlinear behavior in the residuals.